جدلية العلاقة (التضخم - البطالة) دراسة قياسية لحالة الجزائر للفترة 1990- 2020 - بقاط, حنان; محلوس, زكية; بن خليفة, أحمد (جامعة الوادي - University of Eloued, 2021)
نهدف من خلال هذه الدراسة الى التعرف على طبيعة وشكل العلاقة بين البطالة والتضخم في الجزائر خلال الفترة 1980 – 2020، باستخدام بيانات سنوية وبالاستعانة بالاقتصاد القياسي وذلك من خلال اختبار التكامل المشترك حسب جرانجر وجوهانسن و اختبار السببية لجرانجر. وتوصلنا من خلالهم إلى عدم وجود تكامل مشترك بين التضخم والبطالة أي عدم وجود علاقة توازنية طويلة المدى وعدم وجد علاقة سببية بين البطالة والتضخم، وبالتالي يمكن القول بأن البطالة والتضخم لا يرتبطان بعلاقة طويلة الاجل في الاقتصاد الجزائري خلال الفترة 1990- 2020. This study aims to identify the nature and form of the relationship between unemployment and inflation in Algeria during the period 1990 – 2020, Using annual data and using econometrics through the joint integration test by Granger and Johansen and the causality test of Granger. We concluded that there is no common integration between inflation and unemployment, that is, the absence of a long, Thus, unemployment and inflation are not associated with a long-term relationship in the Algerian economy during the period 1990-2020.
Dialectical of the Inflation – Unemployment Relationship Algeria Econometric study case for the period 1990 - 2020
مقال
Keywords: بطالة ; تضخم ; منحنى فيلبس ; تكامل مشترك ; جزائر